Idade da menarca e sibilância/asma: resultados de uma coorte de nascimentos em São Luís – MA - MENDES, Mayara Dailey Freire (2022)
Asthma is a heterogeneous and complex disease, with high morbidity and use of health resources. It causes about 489,000 deaths a year worldwide. The higher prevalence of post-pubertal asthma in women may be due to a pathogenetic role of female sex hormones. The worldwide increase in this prevalence and the downward trend in the age of menarche emphasize the importance of questioning whether there is an association between these variables. Therefore, the general objective of this study is to investigate the effect of age at menarche on the incidence of wheezing/asthma in girls, aged 18 and 19 years, in a birth cohort in São Luís - MA. This is a cross-sectional study nested within a cohort study with individuals born in São Luís - MA, in 1997/1998, included in the RPS cohort consortium, in the research "Determinants throughout the life cycle of obesity, precursors of chronic diseases, human capital and mental health”. Data from the third phase of the mixed cohort (prospective and retrospective), in 2015/2016, with female adolescents aged between 18 and 19 years were used. Data were analyzed in Stata 14.0. Descriptive analysis was performed with calculation of proportions and 95% confidence intervals for categorical variables. Bivariate and multivariate analyzes were performed for the associations, using the chi-square test. A Poisson logistic regression model was used for the association between current wheezing and age at menarche, adjusting for possible confounding factors. Of the 1327 girls, 66.99% were 18 years old and 33.01% were 19 years old; 62.09% were brown/mulatto/cabocla/brunette; 43.33% belong to Class C; 88.24% studied from 9 to 11 years; there was a higher prevalence of age at menarche between 11 and 12 years (50.64%); 2.33% had a family history of an asthmatic father and 2.56% of an asthmatic mother; 2.03% were smokers and 13.94% reported current or previous drug use; regarding current wheezing, 7.01% had wheezing in the last 12 months, most (5.73%) with about 1 to 3 attacks. Factors such as schooling, history of paternal and maternal asthma, drug use and smoking showed an important statistical association. The age at menarche did not show such a relationship. In conclusion, the results obtained in this study showed that age at menarche is not associated with the risk of developing wheezing/asthma during adolescence.